2006
DOI: 10.1007/s10552-005-5383-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Risk Factors for Ovarian Cancer: The Adventist Health Study (United States)

Abstract: Few prospective studies have reported dietary risk factors for ovarian cancer. A total of 71 histologically confirmed epithelial ovarian cancers occurred among 13,281 non-Hispanic white California Seventh-day Adventist women during follow-up. Participants were part of the Adventist Health Study (AHS) and had no history of cancer or hysterectomy at baseline in 1976 when they completed a detailed lifestyle questionnaire including a dietary assessment. The association of dietary variables with either all ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 49 publications
1
45
1
2
Order By: Relevance
“…Additional studies have evaluated the association between flavonoid-rich foods and beverages and ovarian cancer risk. 10, Although some studies have found inverse associations with consumption of certain vegetables and fruits, tea and other dietary sources of flavonoids, 22,[26][27][28]31,33,39,42,45 overall the data are equivocal. The same flavonoid can be present in multiple foods and beverages, which suggests that an association between flavonoid intake and ovarian cancer risk could exist despite the absence of a clear association with consumption of certain flavonoid-rich foods.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have evaluated the association between flavonoid-rich foods and beverages and ovarian cancer risk. 10, Although some studies have found inverse associations with consumption of certain vegetables and fruits, tea and other dietary sources of flavonoids, 22,[26][27][28]31,33,39,42,45 overall the data are equivocal. The same flavonoid can be present in multiple foods and beverages, which suggests that an association between flavonoid intake and ovarian cancer risk could exist despite the absence of a clear association with consumption of certain flavonoid-rich foods.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of the primary data from 12 prospective cohort studies (13,19,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) based in North America and western Europe was conducted in the Pooling Project of Prospective Studies of Diet and Cancer. The methods have been described in detail elsewhere (41).…”
Section: Methodsmentioning
confidence: 99%
“…In the analysis regarding BMI during early adulthood, individuals whose BMI at that time was <14 or >50 kg/m 2 were excluded. The Adventist Health Study (37) and New York State Cohort (29) did not obtain information on oophorectomy at baseline; thus, we were not able to exclude individuals who had a bilateral oophorectomy before baseline in these studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations